Job Satisfaction, Organizational Commitment and Turnover Intention among Restaurant Employees in Pokhara: A Higher Order Construct Assessment in SEM - Subedi, Netra Prasad (Journal of Business and Management, 2025)
Background: Employee retention is not only an indicator of good human resource management but a strategic necessity as well, because it affects directly or indirectly the areas of profitability, customer loyalty, and the culture of the organization. The hotels and restaurants in Nepal have been classified as industries with a very high employee turnover rate.Objective: This study was conducted in Pokhara, Nepal with the aim to identify the influencing factors of employees’ job satisfaction and organizational commitment, and how these factors subsequently influence turnover intention in the restaurants sector.Methods: A quantitative research method was applied with cross-sectional survey. It utilized partial least square structural equation modeling to assess the model and test the proposed hypotheses including 341 respondents’ data.Results: The results indicate that salary still is the most significant predictor of employee satisfaction (β = 0.442). Likewise, the working environment has a significant impact on job satisfaction (β = 0.312), but its influence on organizational commitment is weak (β = 0.084). The results indicate that co-worker relationships significantly boost job satisfaction (β = 0.235) and organizational commitment (β = 0.210), highlighting the importance of cooperative social interactions. Job satisfaction stands out as a key factor influencing organizational commitment (β = 0.566), suggesting that satisfied employees have a stronger emotional connection to their organization. Organizational commitment, including value, effort, and retention commitment, is the strongest buffer against employee’s intention to leave the organization (β = - 0.559), beating job satisfaction (β = -0.328).  Conclusion: The results suggest to give priority to attractive salaries and benefits, healthy co-workers relationship, and facilitating working environment in the restaurant businesses for the job satisfaction of staff, organizational commitment, and reduce turnover intention.